2020
DOI: 10.2139/ssrn.3553867
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Health Insurance: Theory Meets Evidence

Abstract: To insure policyholders against contemporaneous health expenditure shocks and future reclassification risk, long-term health insurance constitutes an alternative to community-rated shortterm contracts with an individual mandate. Relying on unique claims panel data from a large private insurer in Germany, we study a real-world long-term health insurance application with a life-cycle perspective. We show that German long-term health insurance (GLTHI) achieves substantial welfare gains compared to a series of ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…For the time period and states in our sample, insurers could experience rate small employers without significant regulatory restrictions. 5 Related to our study, Buchmueller and DiNardo (2002) investigated whether the implementation of community rating in New York led to adverse selection, while Cutler and Reber (1998); Bundorf et al (2012); Einav et al (2010), and Kowalski (2015) study reclassification risk for employees who could choose from a menu of plans offered by their employer, and Atal et al (2019) study guaranteed renewability contracts in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…For the time period and states in our sample, insurers could experience rate small employers without significant regulatory restrictions. 5 Related to our study, Buchmueller and DiNardo (2002) investigated whether the implementation of community rating in New York led to adverse selection, while Cutler and Reber (1998); Bundorf et al (2012); Einav et al (2010), and Kowalski (2015) study reclassification risk for employees who could choose from a menu of plans offered by their employer, and Atal et al (2019) study guaranteed renewability contracts in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…In the U.S. prior to the ACA, state-level guaranteed renewability regulations introduced some elements of dynamic contracting to health insurance contracts, albeit of a restricted form [Patel and Pauly (2002), ]. Outside of the U.S., both Germany and Chile have some long-term contracting for health insurance [Browne and Hoffman (2013), Atal (2016), Atal et al (2019)].…”
Section: Introductionmentioning
confidence: 99%
“…We find that insuring this pre-age-25 health risk, so that all consumers have the same lifetime welfare as the healthiest 25 year old, would cost the government between $5,000 and $12,000 per consumer. 4 We also examine the welfare effect of a balanced budget insurance scheme for pre-age-25 health risk. With this insurance in place, dynamic contracts close between 79-93% of the ex ante welfare gap between spot contracts and our "No Borrowing / No Saving" benchmark.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hendel and Lizzeri (2003) theoretically and empirically examined how life insurers mitigate reclassification risk by offering front‐loaded policies. More recently, Handel, Hendel, and Whinston (2017) and Atal, Fang, Karlsson, and Ziebarth (2018) showed that front‐loaded long‐term health insurance contracts can produce substantial welfare gains by insuring policyholders against reclassification risk. The main difference between these models and ours is that consumers in our model are dynamically inconsistent.…”
Section: Introductionmentioning
confidence: 99%